ChemInform Abstract: Gold(I)‐Catalyzed Furan‐yne Cyclizations Involving 1, 2‐Rearrangement: Efficient Synthesis of Functionalized 1‐Naphthols and Its Application to the Synthesis of Wailupemycin G. Issue 10 (March 2015) - Chen, Yifeng; Wang, Lu; Sun, Ning; Xie, Xin; Zhou, Xiaobo; Chen, Haoyi; Li, Yuxue; Liu, Yuanhong
Abstract A novel gold‐catalyzed reaction of furan‐ynes bearing a propargylic alcohol moiety leads to multisubstituted 1‐naphthols via a cyclization/1, 2‐rearrangement cascade.